Investigations into the nutritional requirements of juvenile dusky kob, Argyrosomus japonicus (Pisces sciaendae), under ambient culture conditions - Daniel, Simon James (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2004)
The effect of dietary protein, protein and energy ratios, fish meal replacement by Soya bean meal and feeding frequency was investigated on the growth, feed efficiency and body composition, of juvenile dusky kob, Argyrosomus japonicus. The effect of dietary protein levels was investigated by comparing isocaloric diets containing 35, 40, 45 and 55% protein. Dietary protein inclusion level significantly affected specific growth rates, feed efficiency and body composition (in terms of fat deposition) and results show that a minimum of 45% and maximum of 52.3% dietary protein is optimal. The protein and energy requirements were investigated by comparing three protein levels (35,40 and 45%) with three lipid levels (6, 9 and 12%) in a 3x3 factorial design. A diet 45% protein and 9% lipid, with a P: E ratio of29 mglkJ and DE of 15.5 kJ/g resulted in an optimal specific growth rate (1.6± 0.2), feed efficiency (FCR= 1.7±0.44; PER= 1.36) and body composition for A. japonicus. To investigate the effect of partial fish meal replacement by Soya bean meal (SBM) in the diet, 20-50% of the protein from fish meal was substituted by protein from SBM, and were compared with a control diet containing only fish meal. No significant differences in the specific growth rates, feed efficiencies and the body composition were recorded for the fish fed the control diet and for fish fed the 20 and 30% SBM treatments. Results show that up to 30% of the protein from fish meal can be replaced with protein from SBM in the diet of this species. The effect of feeding frequency and gut evacuation time was investigated by comparing four feeding frequencies. Fish were fed to satiation either once, twice, three or four times a day. Feed intake was significantly affected by feeding frequency and fish fed 2, 3 and 4 meals a day ate significantly more food (p< 0.05) than the fish fed one meal a day. No significant differences (p> 0.05) in the specific growth rates, feed efficiencies and body composition were recorded for fish fed 2, 3 and 4 times a day. Feed intake was used to calculate an optimal daily ration and feeding two meals a day resulted in an optimal daily ration of 4% BW/day. A gut evacuation time of 7.25 hours indicates that fish fed twice a day probably had sufficient time to digest their food and evacuate their guts, resulting in the same daily feed intake as fish given 3 and 4 meals a day. Results conclude that under the present experimental conditions, a minimum daily ration of 4% BW/day, fed twice a day (in the morning and evening) is required for optimal growth (SGR= 1.33± 0.1), feed efficiency (FCR= 1.96± 0.4; PER= 1.44± 0.2) and body composition in juvenile dusky kob.
Keywords: Argyrosomus -- Nutrition -- Requirements; Sciaenidae -- Nutrition -- Requirements; Fishes -- Food; Fishes -- Growth; Fish culture; Fishes -- Nutrition -- Requirements